2006
DOI: 10.1101/gad.377106
|View full text |Cite
|
Sign up to set email alerts
|

p27kip1 independently promotes neuronal differentiation and migration in the cerebral cortex

Abstract: The generation of neurons by progenitor cells involves the tight coordination of multiple cellular activities, including cell cycle exit, initiation of neuronal differentiation, and cell migration. The mechanisms that integrate these different events into a coherent developmental program are not well understood. Here we show that the cyclin-dependent kinase inhibitor p27Kip1 plays an important role in neurogenesis in the mouse cerebral cortex by promoting the differentiation and radial migration of cortical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
420
3
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 341 publications
(450 citation statements)
references
References 54 publications
24
420
3
3
Order By: Relevance
“…The coactivator CBP has been shown to be critical for Mash1 activity, whereas the Id family of bHLH-interacting proteins repress the activity of bHLH transcription factors. 39 Earlier studies have shown that p27Kip2 and Neurogenin2 (Ngn2) interacts in the dorsal pallium and developing neocortex 14,17 suggesting in addition to the temporal aspects, a spatial component in the expression and function of different CKIs Reporter gene assays. The E-box reporter plasmid containing region of the MCK enhancer coupled to luciferase, MCK-fos-luc was a gift from Dr. M Sigvardsson.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The coactivator CBP has been shown to be critical for Mash1 activity, whereas the Id family of bHLH-interacting proteins repress the activity of bHLH transcription factors. 39 Earlier studies have shown that p27Kip2 and Neurogenin2 (Ngn2) interacts in the dorsal pallium and developing neocortex 14,17 suggesting in addition to the temporal aspects, a spatial component in the expression and function of different CKIs Reporter gene assays. The E-box reporter plasmid containing region of the MCK enhancer coupled to luciferase, MCK-fos-luc was a gift from Dr. M Sigvardsson.…”
Section: Methodsmentioning
confidence: 99%
“…11,12 In addition, CDK-inhibitors (CKIs) have been shown to play active roles in neural differentiation and migration. 10,13,14 The expression of p21Cip1 in the developing telencephalon is relatively low, but it has been reported that p21Cip1 is essential for the maintenance of adult neural progenitors in the forebrain. 15 p27Kip1 has been implicated in the cell-cycle arrest of neural precursors during forebrain development, and also in oligodendrocytic specification and differentiation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, p27 Kip1 can also participate in the blockage of classical cell cycle progression 9 as well as neuronal differentiation and migration. 71 Therefore, p27 Kip1 is probably playing multiple roles in RGCs, including the blockade of tetraploid neurons to undergo extra rounds of endoreplication and the inhibition of cell cycle reactivation in diploid neurons that have not been programmed to become tetraploid.…”
Section: Discussionmentioning
confidence: 99%